On the Efficiency of Some Selected Designs: A Case of Randomized Block Designs (Global Journal of Science Frontier Research, 2018)
This work examines the Relative Efficiency (RE) of some selected Randomized Complete Block Designs (RCBD).The efficiency of the selected designs showed that design B was the most preferable having Mean Square Error of 6.14, followed by design C with Mean Square Error of 9.11 and design A with Mean Square Error of 18.08. The results from the pair-wise relative efficiency of the selected designs show that RE(B,A) = 0.34 with the smallest relative efficiency value and RE(A,B) = 2.94 with the largest relative efficiency value. We recommended design B as the best design for this particular problem since its mean square error remains the smallest.
Keywords: RCBD; efficiency; missing value and estimation